Comparative Evaluation of the Impact of Capital Structure and Liquidity Management Policies on Financial Stability and Economic Value Added (EVA) of Rural Banks (BPRs) in Yogyakarta Province - Lembong, Herningsih Sutri; Lumapow, Lihard Stevanus; Gumolung, Remart; Oktaviana, Leony; Katiandagho, Chelsia (Westscience Press, 2025)
This study evaluates the comparative impact of capital structure and liquidity management policy on financial stability and Economic Value Added (EVA) of Rural Banks (BPR) in Yogyakarta Province. Using a quantitative approach, data were collected from 50 BPRs through structured questionnaires and analyzed using SPSS version 20. The findings reveal that both capital structure and liquidity management policy significantly and positively influence financial stability and EVA. Liquidity management policy exhibited a stronger effect on both dependent variables, underscoring its critical role in sustaining financial health and enhancing value creation. These results provide actionable insights for BPRs to optimize their financial strategies for improved performance.